Tourists Perception of “Mepantigan”, Balinese Traditional Martial Art as Alternative Tourism Attraction in Gianyar, Bali - Arcana, Komang Trisna Pratiwi; Hani, Trivena; Sudjana, I Made (Institut Pariwisata dan Bisnis Internasional, 2019)
The study examined the perception of tourists on “Mepantigan” as alternative tourism in Pondok Mepantigan in Gianyar Bali. The background of this research is the emergence of “Mepantigan” attraction that is developing. Obviously, “Mepantigan” is a unique and first tourist attraction in Gianyar Bali by elevating traditional martial arts and combined with the art of dance and music with the game set in the mud. The purpose of this study is to identify the perception of tourists to “Mepantigan” as alternative tourism in Pondok Mepantigan in Gianyar Bali. In essence research method using the qualitative and quantitative method. Data analysis techniques used descriptive-qualitative, where data obtained from observation, interview, documentation, and questionnaire to tourism components such as attraction, accessibility, amenities, available packages, activities, and ancillary services. Sustainable tourism paradigm and can be applied to alternative tourism is tourism activity. The research results showed that Pondok Mepantigan is an attractive tourist attraction because it has a natural tourist attraction, culture and artificial but need to increase the availability of supporting facilities for tourists. In essence, Pondok Mepantigan has met the parameters as alternative tourism but need to improve in empowering communities around Pondok Mepantigan.